1024 PROGNOSTIC VALUE OF CI-AKI AND HIS RELATIONSHIP WITH PERIPROCEDURAL MYOCARDIAL DAMAGE IN NSTEMI. (15th December 2022) - Impellizzeri, Andrea; Armillotta, Matteo; Bergamaschi, Luca; Amicone, Sara; Suma, Nicole; Bodega, Francesca; Canton, Lisa; Fedele, Damiano; Sansonetti, Angelo; Angeli, Francesco; Foà, Alberto; Rinaldi, Andrea; et al.
Abstract: Background: Periprocedural myocardial damage and contrast-induced acute kidney injury (CI-AKI) are frequent complications of percutaneous coronary intervention (PCI) and impact prognosis. The possible associations and the prognostic role of these peri-procedural complications are still not well understood. Purpose: To evaluate predictors and prognostic role of CI-AKI in patients with NSTEMI and the relationship between CI-AKI and periprocedural myocardial damage. Methods: Patients with NSTEMI undergoing coronary angiography within 72 hours were enrolled from January 2016 to September 2021. To detect post-PCI acute myocardial damage in this setting of NSTEMI patients, we included only those with stable (≤ 20% variation) or falling pre-procedure baseline cardiac troponin (cTn) values. Serum cTnI were measured at baseline and at 3-6-12 hours after PCI in all patients. Periprocedural myocardial damage was evaluated according to postprocedural hsTnI criteria provided by most recent consensus documents. Renal injury was documented when absolute serume creatinine increased of ≥ 0.3 mg/dL or ≥ 50% within 72 hours or urine output reduced to ≤ 0.5 mL/Kg/hour for at least 6 hours. Results: We enrolled 878 patients with NSTEMI undergoing PCI and with pre procedure stable cTn levels. 53 patients suffered from AKI post contrast and among these 8 patients exhibited myocardial periprocedural injury and 20 patients had periprocedural myocardial infarction according to European Society of Cardiology guidelines. Myocardial periprocedural damage occurred more frequently in the CI- AKI group compared to non-CI-AKI group (52% vs 38%, p = 0.01). Patients who experienced CI-AKI were significantly older (mean age 86 ± 4) and had more frequently cardiovascular risk factors such as diabetes (p < 0.001) and hypertension (p = 0.006), compared to non-CI-AKI group. Moreover NSTEMI patients with CI-AKI were more often on beta-blockers (p= 0.001) and statins (p < 0.001) and exhibited more frequently at admission ST-T segment (p < 0.000) and wall motion alterations at echocardiography evaluation (p = 0.004).Regarding intra-hospital outcomes, CI-AKI population experienced more frequently reinfarction (p = 0.02) and arrhythmias (p < 0.000) compared to others . Surprisingly, the multivariate logistic regression showed that the stronger predictor of CI-AKI was periprocedural myocardial infarction (p < 0.001). Finally, at 3 years of follow-up, in patients with CI-AKI there was more incidence of all-cause mortality (p = 0.001) and the composite of all-cause death, re-acute myocardial infarction and hospitalization for heart failure (p = 0.05) compared to non-CI-AKI group. Conclusion: In NSTEMI patients, contrast-induced acute kidney injury was associated with majors adverse events, both intra-hospital and at long-term follow-up. Subjects who experienced acute kidney injury were older, had more comorbidities and had a worse clinical and instrumental profile at admission. CI-AKI was also associated with peri-procedural acute myocardial injury and infarction. More studies are needed to understand the patophysiological relations between these to post-PCI complications to improve their management.